The ethical implications of artificial nutrition and hydration in end-of-life care: a comprehensive review - Karaboue, Michele; Lacasella, Giorgia (Progress in Nutrition, 2024)
This article explores the multifaceted ethical dimensions of Artificial Nutrition and Hydration (ANH) in the context of end-of-life care. It delves into the debate over whether ANH should be considered a medical intervention or a basic human right, examining the symbolic significance of feeding and hydration in social and moral relationships. This work discusses the National Committee for Bioethics' standpoint on the moral obligation to provide food and fluids to patients in need, highlighting the complex interplay between medical necessity and ethical duty. This review also scrutinizes the classification of ANH as either a form of medical treatment or a basic human need, and its implications for decisions about initiating or discontinuing such interventions. Analyze the moral and practical considerations surrounding the suspension or non-initiation of ANH, emphasizing the importance of context and individual patient values in these decisions. The discussion underscores the dilemma faced by healthcare providers and caregivers in balancing the symbolic value of ANH against its clinical utility, especially in cases where prolongation of life might conflict with the patient's perceived quality of life. The article concludes by advocating for a nuanced, context-sensitive approach to ANH decisions, where careful ethical deliberation is paramount to ensure that the rights and dignity of patients at the end of life are respected and upheld.